APPLICATION OF FIVE-STREAM FRAMEWORK CONCEPT IN E-PROCUREMENT IMPLEMENTATION IN DEPOK: A REVIEW OF LITERATURE - Nuurul Fajari Fadhillah; Vishnu Juwono (DIA: Jurnal Administrasi Publik, 2020)
In the current digital era, technology distribution in all sectors is crucial, no exception in the procurement of goods and services sector. Knowing this situation, the government then makes a policy that requires the process of procurement done electronically through the e-procurement application. By implementing this policy, the government expects an improvement of transparency, accountability, and efficiency in the process of procurement. To support this effort, in the year 2018 government also issued the Peraturan Presiden No. 16 Tahun 2018 on Public Procurement of Goods and Services, which provides an expansion of the role for stakeholders to engage in the process of procurement.One of the cities that implement e-procurement is Depok through its Working Unit for Procurement of Goods and Services (UKPBJ). This city even received numerous awards while implementing this policy. Nevertheless, there are many high fraud potential and corruption cases in this sector in the last few years. Through this research, the author seeks to provide recommendations of e-procurement implementation in Depok based on the public policy implementation concept from Howlett (2018), which does emphasize the importance of stakeholder role. The data on this research is gathered through the literature review methods while still paying attention to the credibility of data sources. The results of the analysis using this concept preceded by stakeholder mapping based on Emmy (2015) explanation show that the stakeholder role is crucial and must be maintained. Besides, efforts to increase transparency are also needed to facilitate stakeholders doing their role.